2010
DOI: 10.1038/jid.2009.335
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 Is Upregulated in Melanoma Metastasis Compared with Primary Melanoma

Abstract: ADAM10 (a disintegrin and metalloproteinase 10) is involved in the ectodomain shedding of various substrates, including adhesion molecules such as L1 cell adhesion molecule (L1-CAM) and CD44, which are known to have important roles in the development of malignant melanoma. In our study, we characterized the expression of ADAM10 in melanoma cells in vitro and in vivo. Immunohistochemical analysis on tissue microarrays indicated that ADAM10 expression was significantly elevated in melanoma metastasis compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 44 publications
5
83
2
6
Order By: Relevance
“…S3) have already been identified by us in the secretome of mesenchymal cells in the context of tumorassociated inflammation (55). CD44 shedding has directly been linked to calcium mobilization and contributes to metastasis (56). The interrelation between inflammation, calcium, reactive oxygen species and specific stress signatures like endoplasmic reticulum stress is well established (57).…”
Section: Discussionmentioning
confidence: 99%
“…S3) have already been identified by us in the secretome of mesenchymal cells in the context of tumorassociated inflammation (55). CD44 shedding has directly been linked to calcium mobilization and contributes to metastasis (56). The interrelation between inflammation, calcium, reactive oxygen species and specific stress signatures like endoplasmic reticulum stress is well established (57).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Among them, ADAM10 is known to be involved in tumour progression. 11,12,16,17,26 It has been reported that ADAM10 can cleave collagen type IV in the basement membrane, which is relevant to tumour metastasis. 11 Murai et al showed that the cleavage of CD44 catalyzed by ADAM10 contributed to the migration and invasion of glioblastoma tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of ADAMs, including ADAM9, ADAM10, ADAM12 and ADAM17, are critical during the genesis, development and metastasis of cancers (21,25,26). Dysregulated expression of ADAM10 has been reported in various malignancies, and has been suggested to be involved in cancer progression (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ADAM family members, including ADAM10, serve pivotal roles in the pathogenesis or progression of cancers, including proliferation, angiogenesis, migration and invasion (6)(7)(8)(9). Analysis of gene expression profiles revealed that the ADAM10 gene was significantly overexpressed in a wide variety of human malignancies, including hepatocellular carcinoma, melanoma, oral squamous cell carcinoma, lung cancer, pancreatic carcinoma, and gastric and bladder cancer (10)(11)(12)(13)(14)(15)(16)(17). Accumulating evidence has illustrated that ADAM10 contributed to the regulation of cancer progression, chemoresistance and metastasis via the cleavage of growth factors or cell surface proteins (6,8,10,12,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation